The Pivotal Role of Women in Cardiology Sections in Medical Organizations: From Leadership Training to Personal Enrichment - Garima Sharma, MD; Sandra Lewis, MD; Toniya Singh, MD; Laxmi S. Mehta, MD; Jennifer Mieres, MD; Athena Poppas, MD; Robert Harrington, MD; Ileana L. Piña, MD, MPH; Annabelle Santos Volgman, MD; Niti R. Aggarwal, MD (CJC Open, 2021)
Women in cardiology (WIC) sections have emerged as important leadership, career development, and advocacy forums for female cardiologists. Over the past 3 decades, they have grown from small groups to large sections within volunteer science organizations. In addition to providing a sense of community and promulgating the principles of diversity, equity, inclusion, and belonging, the WIC sections have contributed to improving workplace culture and dynamics by generating evidence-based and actionable data, fostering leadership by and scientific enrichment of women, developing task forces and health policy documents targeted toward reduction of burnout and bias in medicine, and providing a platform to voice the unique challenges and opportunities of female cardiologists. The future holds great promise, as the WIC sections continue to play a pivotal role by being intentional, transparent, iterative, and sustainable, and working with important stakeholders, including men, to share data, best practices, and strategies to create and maintain a culture of equity and achieve its core principles. Résumé: Les sections WIC (“Women In Cardiology”) des femmes en cardiologie sont devenues d'importants forums de leadership, de développement de carrière et de défense des intérêts des femmes cardiologues. Au cours des trois dernières décennies, leur potentiel est passé de petits groupes à de grandes sections au sein d'organisations scientifiques bénévoles. En plus de donner un sentiment d'appartenance à une communauté et de promouvoir les principes de diversité, d'équité, d'inclusion et d'appartenance, les sections WIC ont contribué à améliorer la culture et la dynamique du milieu de travail en proposant des données factuelles et exploitables, en encourageant le leadership et l'enrichissement scientifique des femmes, en créant des groupes de travail et des documents de politique de santé visant à réduire l'épuisement professionnel et les préjugés en médecine, et en offrant une plateforme pour exprimer les défis et les opportunités uniques des femmes cardiologues. L'avenir semble très prometteur puisque les sections WIC continuent de jouer un rôle central en étant conscientes, transparentes, itératives et durables et en travaillant avec des parties prenantes importantes, y compris masculines, pour partager des données, des meilleures pratiques et des stratégies afin de créer et d'en maintenir la culture et de concrétiser ses principes fondamentaux.